FINANCIAL LITERACY LEVEL OF YOUNG ENTREPRENEURS IN THE PRIVATE UNIVERSITY - Chalidana, Moehamad Yunus; Radianto, Wirawan ED; Hengky, Alexander Wahyudi; Efrata, Tommy Christian (Jurnal Aplikasi Manajemen, 2020)
This study aims to illustrate how high the level of financial literacy is amongst young entrepreneurs descriptively. Young entrepreneurs are students who have a business project during their studies at the university. The research methodology used in the study is the survey method by sending out questionnaires to respondents. There are in total of 183 respondents that were successfully collected. The data analysis methodology used is descriptive statistics evaluation. The study foundings indicates that the financial literacy of young entrepreneurs is considered in the low category. Young entrepreneurs better understand savings and loans than understanding insurance.